Accountability in waqf mangement: learning from praxis of nongovernmental organization (NGO) - Osman, Ahmad Zamri (2010)
The paper aims to examine the way in which improvement on the effectiveness and efficiency of waqf management may be made through its relationship with beneficiaries, in this case the poor. The study uses accountability as the main conceptual lens informing this relationship. Although there are many ways to improve waqf management,it is important that the relationship of waqf management with beneficiaries must be given due consideration. This consideration does not merely see participation of beneficiaries as the passenger in the relationship, i.e., sitting at the receiving ends of the relationship or the assistance receiver/the poor. Rather, the relationship should look at the relationship as one of the means to improve management of waqf. Drawing from accountability literatures especially NGO accountability and the notion of participative accountability, the paper looks at the potential of the notion of downward accountability to augment the conventional upward accountability. In other words, while effort to improve the effectiveness of waqf management tends to focus on upward reporting and accountability to board of trustee akin to corporate style reporting to board of director, there may be a huge potential to listen to and to have dialogue ‘downwardly’ to beneficiaries. Stated differently, an improved accountability relationship downwardly to beneficiaries offers an opportunity for an improvement on the effectiveness and efficiency of waqf management. This is essentially a conceptual paper in which the empirical study is in progress. In presenting the conceptual elements, the paper draws experience from NGO literature especially literatures on NGO accountability and explore the extent to which improved accountability relationship towards the poor may improve the effectiveness and efficiency of waqf management.